Ethnocultural Memory and National Identity: The Concept of "Self" and "Other" in Russian and Uzbek Historical Prose - Djuraeva , Farahbonu (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
Cultural identity construction intrinsically relies on the cognitive opposition of alterity. This study interrogates the systemic representations of the "Self" and "Other" concepts within the chronotopes of Russian and Uzbek historical prose. Analyzing a combined textual corpus of 856,420 words, including seminal works by A. Ivanov and P. Kadyrov, the research applies a hybrid methodology of contextual-semantic analysis and statistical corpus processing. Quantitative extraction yielded 2,340 dominant lexical markers delineating binary sociocultural boundaries. Textual evidence indicates a statistically significant divergence in conceptual mapping. Russian historical narratives predominantly spatialized the "Other", anchoring alterity in frontier topography and geographical isolation (64.3% of contexts). Conversely, Uzbek literary matrices localized the "Other" internally (71.2%), utilizing intense socio-hierarchical and religious-philosophical discourse to delineate boundaries. Interpreting these results through Bakhtinian dialogism and Lotman’s semiosphere reveals how specific historical trajectories forge divergent cognitive architectures. The findings offer a novel comparative framework for translation studies and intercultural didactics, optimizing cross-cultural comprehension in academic settings.